Estudo da Imunorreação do Anticorpo Monoclonal Ki-67 (MIB-1) e dos Receptores de Estrogênio e Progesterona no Carcinoma de Mama de Mulheres Tratadas com Tamoxifeno em Baixa Dosagem - Sousa, Juarez Antônio de [UNIFESP] (2006)
Breast carcinoma is the most common malignancy among women, and it has a major impact on mortality. Studies of primary chemoprevention with tamoxifen have generated high expectations and considerable success rates. The efficacy of lower doses of tamoxifen is similar to that seen with the standard dose of the drug, and there is a reduction in medical care costs and adverse effects. The immune reaction to monoclonal antibody Ki-67 (MIB-1) and the expression of estrogen receptors (1D5) and progesterone receptors (PgR 636) in breast carcinoma were studied in patients treated with 10 mg of tamoxifen for a period of 14 days. A prospective randomized clinical trial was conducted with 38 patients divided into two groups: Group A: N = 20 (control group–without medication) and Group B: N = 18 (tamoxifen/10 mg/day for 14 days). All patients signed an informed consent term previously approved by both institutions (UNIFESP-EPM and Hospital Materno Infantil, Goiânia-GO). Patients underwent incisional biopsy before treatment and 14 days later a sample of tumor tissue was obtained during surgical treatment. Positivity was quantitatively assessed, counting at least 1.000 cells per slide. For statistical data analysis, a Wilcoxon non-parametric test was used, and α was set at 5%. Both groups (A and B) were considered homogeneous regarding control variables. In Group A (control), there was no statistically significant reduction in Ki-67 (MIB-1) (p=0.627), estrogen receptor (1D5) (p=0.296) and progesterone receptor positivity (PgR 636) (p=0.381). In Group B (tamoxifen 10 mg/day), the mean percentage of nuclei stained by Ki- 67 (MIB-1) was 24.7% before and 10.4% after tamoxifen treatment. Mean percentage of nuclei stained by estrogen receptor (1D5) was 59.5% before and 25.9% after tamoxifen treatment. Mean percentage of nuclei stained by progesterone receptor (PgR 636), was 59.3 before and 29.6% after tamoxifen treatment. A statistically significant reduction was found with the three markers (p<0.001). Tamoxifen significantly reduced monoclonal antibody Ki-67 (MIB-1), estrogen receptor (1D5) and progesterone receptor positivity (PgR 636) in the breast epithelium of patients with carcinoma, treated with a 10 mg dose of tamoxifen for 14 days.